Linalool reverses neuropathological and behavioral impairments in old triple transgenic Alzheimer's mice (2016)
ABSTRACT: Alzheimer’s disease (AD) is an age-related progressive neurodegenerative disorder. Several types of treatments have been tested to block or delay the onset of the disease, but none have been completely successful. Diet, lifestyle and natural products are currently the main scientific focuses. Here, we evaluate the effects of oral administration of the monoterpene linalool (25 mg / kg), every 48 hours for 3 months, on aged (21–24 months old) mice with a triple transgenic model of AD (3xTg-AD) mice. Linalool-treated 3xTg-AD mice showed improved learning and spatial memory and greater risk assessment behavior during the elevated plus maze. Hippocampi and amygdalae from linalool-treated 3xTg-AD mice exhibited a significant reduction in extracellular β-amyloidosis, tauopathy, astrogliosis and microgliosis as well as a significant reduction in the levels of the pro-inflammatory markers p38 MAPK, NOS2, COX2 and IL-1β. Together, our findings suggest that linalool reverses the histopathological hallmarks of AD and restores cognitive and emotional functions via an anti-inflammatory effect. Thus, linalool may be an AD prevention candidate for preclinical studies.